Neobešika Belgrade pouch: metabolička razmatranja - Bančević, Vladimir; Aleksić, Predrag; Stamenkovic, Dusica; Pejcic, Tomislav; Milovic, Novak; Kovačević, Božidar; Cerović, Snežana (Vojnosanitetski pregled, 2016)
Background/Aim. The ileal neobladder should be a low-pressure reservoir with acceptable volume and relatively small resorptive surface. A larger inner surface of the ileal pouch is associated with the high resorption of urine metabolites through intestinal mucosa and systemic metabolic disturbances, while a too small pouch results in a higher frequency of voiding and incontinency. The aim of this study was to investigate it is possible to create a neobladder from a shorter ileal segment compared to standard surgical techniques, and reduce metabolic complications. Methods. This prospective study included 77 male patients, scheduled for radical cystectomy and orthotopic neobladder derivation. The patients were divided into two groups: the standard pouch (SP) group of 37 patients scheduled for standard orthotopic neobladder, using a 50−70 cm long terminal ileum segment; the “Belgrade pouch” (BP) group of 40 patients scheduled for original, orthotopic urinary reservoir, using a 25−35 cm long terminal ileum segment. We measured neobladder capacity, acidosis, base excess and bicarbonate concentration in the postoperative month 3rd, 6th, 12th and 15th. Results. At the end of the study, the patients from the SP group had much higher neobladder capacity than the natural bladder − 750 mL (range 514−2,050 mL); in contrast, the patients from the BP group had average capacity of 438 mL (range 205−653 mL) (p < 0.001). At the end of the study, there were more patients with acidosis (37.8% : 2.5%), base excess (35.1% : 7.5%) and low bicarbonate level (40.5% : 20.0%) in the SP group, than in the BP group, respectively (p < 0.001). Conclusion. “Belgrade pouch”, make from 25−35 cm long terminal ileum segment may obtain adequate capacity and lower rate of metabolic disturbances than standard, high capacity orthotopic neobladders.